Nitrogen Accumulation, Use Efficiency, and Productivity of Wheat (Triticum aestivum L.) as Influenced by Different Rates of Nitrogen in Lalitpur, Nepal - Nabin Rawal; Shree Prasad Vista; Dinesh Khadka; Narayan Khatri; Prakash Paneru (Applied and Environmental Soil Science)
Appropriate application of nitrogen (N) not only increases wheat production but also results in optimum N use efficiency (NUE). An experiment was conducted to determine the N concentration, uptake, use efficiency, and performance of wheat in response to N fertility levels at Khumaltar, Lalitpur, Nepal, during 2019/20 and 2020/21. The experiment involved 7 treatments; 6 levels of N (0, 50, 75, 100, 125, and 150 kg ha−1) with application of P2O5:K2O in 50:50 kg ha−1, and zero plot (no fertilizer application), which was laid out in randomized complete block design and replicated three times. The varying N had a significant influence on grain yield, N concentration, its uptake, NUE, and the economics of wheat production. Two years of pooled grain yield showed significantly (p≤0.001) higher grain yield (6.52 Mg ha−1) with a B: C ratio of 2.6, observed from the application of 150 kg N ha−1, which was at par with the use of N @ 125 kg ha−1 (6.32 Mg ha−1). The 2-year mean N concentration in grain and straw of wheat was 13.98 and 3.49 g kg−1, respectively. The data revealed that 4.9 Mg ha−1 grain yield plus 5.56 Mg ha−1 dry straw yield removed 81.7 kg N ha−1. Likewise, the N partition in wheat grain and straw was 75% and 25% respectively. The mean partial factor productivity, internal efficiency, physiological efficiency, recovery efficiency, and agronomic efficiency of N in wheat were found to be 61.8 kg kg−1, 59.1 kg kg−1, 53.1 kg kg−1, 45.0%, and 22.5 kg kg−1, respectively. N was a limiting nutrient as added N fertilizer had a considerable impact on wheat production and the use of 125 kg N ha−1 was recommended under similar soil properties and ecology.